Experiment and Simulation Research on Performance of Single Transistor of CCD On-chip Amplifier Induced by Proton Irradiation - YAN Shixing1, WANG Zujun1, 2, TANG Ning1, LYU Yubing3, WANG Xiaodong3, LI Chuanzhou1, JIANG Rongyu1 (Yuanzineng kexue jishu)
The irradiation-induced performance degradation of CCD (charge coupled device) image sensors is closely related to the performance degradation of MOS (metal oxide semiconductor) transistors in CCD on-chip amplifiers. The damage mechanism and annealing effect of proton irradiation-induced performance degradation of MOS transistors in CCD on-chip amplifiers were investigated to provide theoretical and experimental support for the study of proton radiation damage effect and annealing effect in CCD image sensors. Taking the MOS transistors in domestic CCD on-chip amplifiers as the research object, proton irradiation experiments with three different fluences were carried out, and the degradation of the performance parameters before and after irradiation was tested. In order to simulate the real situation of MOS transistors in CCD on-chip amplifiers before and after irradiation, the process model of MOS transistors in CCD on-chip amplifiers was established by SENTAURUS TCAD software according to the actual process parameters of the devices, and the simulation model was calibrated and verified according to the actual test data before and after irradiation experiments, and relevant physical models were introduced. Fixed positive charges were introduced into the SiO2 layer and interface states were introduced at the Si/SiO2 interface to simulate the radiation damage effect, and the irradiation simulation results are in good agreement with the irradiation experimental test results. Combined with the irradiation experimental data and simulation results, the proton irradiation damage effect of the MOS transistors in the CCD on-chip amplifier was analyzed in depth, and the results show that the changes of irradiation parameters such as threshold voltage and saturation output current are mainly caused by the radiation induced oxide trap charge and interface state, and the amount of trap charges induced by radiation is correlated to the size of proton irradiation fluence, and the irradiated device threshold voltage increases, saturation output current decreases, and irradiation induced trap charge is correlated to the size of proton irradiation fluence. After irradiation, the threshold voltage of the device increases, the saturation current decreases, and the larger the amount of irradiation fluence, the greater the change of electrical characteristics parameters. Finally, the room temperature annealing test was also carried out to study the annealing effect on the electrical parameters of the CCD on-chip amplifier MOS transistors after proton irradiation, and the test results show that with the extension of the annealing time, the threshold voltage and saturation output current of the device recover to a certain extent.